(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article provides a comparative analysis of the organization and functioning of the patronage service in two administrative-territorial units of Uzbekistan – the city of Tashkent and the Tashkent region. The study focuses on key aspects: regulatory framework, organizational structure, staffing, financing, population coverage and material-technical base. Significant differences have been identified, due to the urbanized nature of the metropolis and the agrarian-rural structure of the region, which affect logistics, service density and the specifics of care provided. Based on the analysis, practical recommendations have been formulated to optimize the work of the patronage service, taking into account regional specifics, aimed at improving the accessibility and quality of primary health care for different population groups.